Penerapan Model Pembelajaran Kooperatif Tipe STAD Untuk Meningkatkan Motivasi Dan Hasil Belajar PAI Tentang Zakat Bagi Siswa Kelas VI SD Negeri 1 Sumberagung Semester II Tahun Pelajaran 2021/2022 - Zubaidi; Abdul Kholiq (Jurnal Studi Islam dan Sosial, 2020)
This study aims to determine the application of the STAD type cooperative learning model to increase motivation and PAI learning outcomes about zakat for class VI SD Negeri 1 Sumberagung semester II 2021/2022 academic year. The results show that the application of the STAD type cooperative learning model can increase motivation and PAI learning outcomes about zakat for grade VI students of SD Negeri 1 Sumberagung in the second semester of the 2021/2022 academic year. In pre-cycle conditions using conventional techniques, students who have high motivation in learning only reach 5.6%, and the value of student learning outcomes reaches an average of 65.55 with a completeness level of 27.59%. After taking action through the application of the STAD type cooperative learning model with homogeneous groups in the first cycle, students who have high motivation in learning reached 18.5%, and the value of student learning outcomes increased to an average of 73.59 with a completeness level of 58.62 %. And then improvements were made to the implementation of the STAD type cooperative learning model with heterogeneous groups in cycle II, students who had high motivation in learning reached 82.8%, and the value of student learning outcomes reached an average of 81.41 with a completeness level of 100%